Two new species of Ampithoidae (Crustacea: Amphipoda) from northeastern Brazil - Andrade, Luiz F.; Senna, André R. (Zootaxa, 2017)
Two new species of the family Ampithoidae Stebbing, 1899 are described from northeastern Brazilian waters. The newly described species belong to the genera Ampithoe Leach, 1814 and Cymadusa Savigny, 1816. Ampithoe robustimana sp. nov. is characterized by: gnathopod 1 propodus elongated, robust and subrectangular, palm almost transverse with a mid-palmar subquadrate tooth; gnathopod 2 propodus elongated, robust and subrectangular, palm almost transverse. Cymadusa ygara sp. nov. is established based on a unique female holotype and is characterized by: antenna 1 accessory flagellum 2-articulate; gnathopod 2 palm slightly concave with a stout setae defining palm; coxae 2–5 bilobate. The examined material of Ampithoe robustimana sp. nov. was collected at Pacheco beach, municipality of Caucaia, Ceará state, while type material of Cymadusa ygara sp. nov. is from Icapuí beach, also in Ceará state.